2021
DOI: 10.1029/2020jd033368
|View full text |Cite
|
Sign up to set email alerts
|

Southern Ocean Cloud Properties Derived From CAPRICORN and MARCUS Data

Abstract: While the region is known for deep midlatitude cyclones, it is the accompanying fields of marine boundary layer (MBL) clouds that seem to be critical to understanding the radiative energy balance of this region (Bodas-Salcedo et al., 2012, 2014, 2016, 2019). Inspired by Trenberth and Fasullo (2010), who showed a high bias in surface-absorbed solar energy by models, studies have increasingly focused on the ubiquity of supercooled liquid water in SO clouds. Simulations of these clouds too aggressively reduce clo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 91 publications
(190 reference statements)
5
30
0
Order By: Relevance
“…However, since we are considering cloudy environments, we can reasonably assume that the humidities in the sub cloud region are likely at least near ice saturation or ~80% with respect to water. This is in agreement with the radiosonde data that we have examined (Mace et al, 2021). For humidities in excess of 60% with respect to liquid, the depolarization ratio of sea salt aerosol is much less than 0.03 (Haareig et al, 2017;their Figure 12).…”
Section: Methods and Data Usedsupporting
confidence: 90%
See 2 more Smart Citations
“…However, since we are considering cloudy environments, we can reasonably assume that the humidities in the sub cloud region are likely at least near ice saturation or ~80% with respect to water. This is in agreement with the radiosonde data that we have examined (Mace et al, 2021). For humidities in excess of 60% with respect to liquid, the depolarization ratio of sea salt aerosol is much less than 0.03 (Haareig et al, 2017;their Figure 12).…”
Section: Methods and Data Usedsupporting
confidence: 90%
“…We only use MARCUS data collected between early January and March 2018 due to insufficient quality lidar data collected earlier. Mace and Protat (2018) and Mace et al (2021) describe the method used to identify MPC occurrence from the surface-based data. By examining warm layers where ice is not possible and ice-only layers, such as snow below cloud base, we identify the depolarization ratio threshold that separates ice hydrometeors from water droplets.…”
Section: Methods and Data Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…MWACR data are calibrated by adding 4.5 dB to the reflectivity profiles provided by ARM. This value was deduced from evaluations of the MARCUS MWACR reflectivity against the calibrated W-band cloud radar onboard the CAPRICORN-II voyage over similar latitudes and times (Mace et al, 2021), and is consistent with the ARM cloud radar offsets identified by Kollias et al (2019). The MWACR was mounted on a stabilizing platform which helped ensure that it remained vertically pointing, although as we will detail below, the ship's heave, pitch, and roll during the three case studies was minimal.…”
Section: Data and Analysissupporting
confidence: 55%
“…Many field campaigns took place in the Southern Ocean to study cloud microphysical and radiative properties (McFarquhar et al, 2020). Mace, Protat, et al (2020) have shown that Southern Ocean clouds tend to be thicker with smaller and more numerous hydrometeors than other latitudes. With airborne measurements, Ahn et al (2017) showed that 38.5% of the clouds contained ice, mainly from mixed-phase clouds, and they suggested that these clouds were considered as ideal for the Hallet-Mossop secondary ice production process.…”
mentioning
confidence: 99%